2018
DOI: 10.1016/j.bjm.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of enteric viruses circulating in a dog population with low vaccine coverage

Abstract: Although the use of vaccines has controlled enteric diseases in dogs in many developed countries, vaccine coverage is still under optimal situation in Brazil. There is a large population of nonimmunized dogs and few studies about the identification of the viruses associated with diarrhea. To address this situation, stool samples from 325 dogs were analyzed by polymerase chain reaction for the detection of common enteric viruses such as Canine adenovirus (CAdV), Canine coronavirus (CCoV), Canine distemper virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 24 publications
(55 reference statements)
8
23
3
1
Order By: Relevance
“…The age range of these animals was considerably heterogeneous, ranging from 40 days to 18 years. In some studies, the mean age was 34.5 months (±41.2) [30,4244]. Regarding the general age profile of the animals, only a few authors specified this profile in detail.…”
Section: Resultsmentioning
confidence: 99%
“…The age range of these animals was considerably heterogeneous, ranging from 40 days to 18 years. In some studies, the mean age was 34.5 months (±41.2) [30,4244]. Regarding the general age profile of the animals, only a few authors specified this profile in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Eleni and colleagues in Central-South Italy demonstrated that CPV was the main causative agent of death in dogs under 1 year of age [27]. Other studies in diarrheic dogs showed lower prevalence of this virus, with a range from the 16% up to 54.3% [10,51,52]. CPV is characterised by high morbidity (100%) and mortality (up to 91%) [53]; thus, it is likely that the inclusion criteria of living dogs could be the main cause of difference with the other studies [10], making it challenging to compare the results.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the dogs in that study were reportedly vaccinated against CDV, but had likely not received a full course of vaccination (Calderon et al 2007) [EB1]. Other studies confirm that CDV is present in Brazil (Budaszewski et al 2014, Monteiro et al 2016, Alves et al 2018), Chile (Acosta-Jamett et al 2011, Colombia (Espinal et al 2014), Cuba (González-Chávez et al 2017), Ecuador (DiGangi et al 2019 including the Galápagos Islands (Levy et al 2008 (Gizzi et al 2014) [EB1]. Other studies show that CPV2 is present in Argentina (Calderón et al 2011(Calderón et al , 2015, Brazil (Alves et al 2018, Headley et al 2018, Chile (Acosta-Jamett et al 2015), Colombia (Duque-García et al 2017), Cuba (Pino-Rodríguez et al 2018), Ecuador (Levy et al 2008, Aldaz et al 2013, De la Torre et al 2018, DiGangi et al 2019, Mexico (Ortega et al 2017) and Uruguay (Pérez et al 2007, Puentes et al 2012, Maya et al 2013 [EB1].…”
Section: Canine Distemper Virusmentioning
confidence: 94%